Bioprospecção de fungos produtores de celulases da região amazônica para a produção de etanol celulósico - Delabona, Priscila da Silva (Universidade Federal de São Carlos, 2011)
Prospecting for cellulose-producing fungi is one of the possible strategies for obtaining the necessary enzymes to hydrolyze the lignocellulosic material and to contribute to the viability of cellulosic ethanol production. Among the different biomes, the Amazon represents a potential source of cellulolytic fungi due to its unique soil and climatic conditions that favor the continued degradation of the biomass of the forest undergrowth. In this context, the objective of this study was the isolation and selection of fungi producing complex cellulase present in the Amazon biome with high efficiency through the process of solid-state fermentation (SSF) of 100 soil samples collected at 50 different points of Reserve Embrapa Eastern Amazon, in Belém - PA. After isolation of fungi, a total of 110, they were transferred to plates containing crystalline cellulose (Avicel) as sole carbon source for selection. Of these 110, 10 fungi were selected that showed the highest growth. The selected strains were grown at 35 ° C for 120 hours in SSF, using as a substrate for a first selection of strains producing endoglucanases, wheat bran with 60 % humidity. The two fungi had higher enzyme production in wheat bran, Aspergillus fumigatus (P40M2) and Aspergillus niger (P47C3) were evaluated in several other substrates, with different percentage of humidity. In these other substrates, has also evaluated the production of endoglucanases, Fpase, xylanase and β- glucosidase.The fungus Aspergillus fumigatus P40M2 showed, in general, the best production of these enzymes. So, finally, the enzymes produced by Aspergillus fumigatus P40M2 were characterized optimum pH, optimum temperature and thermal stability, and their bands of activities identified by electrophoresis (zymograms). The extract obtained by the fungus is characteristic thermophilic and acidophilic being very important for hydrolysis of biomass to ethanol production.
Bioprospecting of cellulase fungi producer in the amazon region for production cellulosic ethanol
Keywords: Biotecnologia; Bioma amazônico; Celulase; Fermentação em estado sólido; Fungos; Amazon biome; Cellulases; Solid state fermentation; Fungal; CIENCIAS BIOLOGICAS::MICROBIOLOGIA